2023
DOI: 10.1021/acs.accounts.3c00402
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls in RNA Modification Quantification Using Nucleoside Mass Spectrometry

Gregor Ammann,
Maximilian Berg,
Jan Felix Dalwigk
et al.

Abstract: Conspectus In recent years, there has been a high interest in researching RNA modifications, as they are involved in many cellular processes and in human diseases. A substantial set of enzymes within the cell, called RNA writers, place RNA modifications selectively and site-specifically. Another set of enzymes, called readers, recognize these modifications which guide the fate of the modified RNA. Although RNA is a transient molecule and RNA modification could be removed by RNA degradation, a subclass of enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Considerations range from susceptibility to oxidation, nucleophilic attacks, and rearrangement to reactions with solvents and chemicals used during the workflow. [9,[12][13][14][15]24] In addition to the previously reported reaction of the cyclic active ester ct 6 A with amines to form amides, the present study showed that esterification with hydroxyl groups, e. g. in glycerol, can also occur. [14,16,17] Although such derivatives have no biological function themselves, they would escape the quantification of their parent compounds, e. g. ct 6 A, thereby leading to misinterpretation of quantitative results.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Considerations range from susceptibility to oxidation, nucleophilic attacks, and rearrangement to reactions with solvents and chemicals used during the workflow. [9,[12][13][14][15]24] In addition to the previously reported reaction of the cyclic active ester ct 6 A with amines to form amides, the present study showed that esterification with hydroxyl groups, e. g. in glycerol, can also occur. [14,16,17] Although such derivatives have no biological function themselves, they would escape the quantification of their parent compounds, e. g. ct 6 A, thereby leading to misinterpretation of quantitative results.…”
Section: Discussionsupporting
confidence: 79%
“…In line with the efforts of some groups in this direction, including proposed strategies to avoid artifacts as well as a classification and characterization of different error sources, our results underline the need for special caution not only in the context of LC-MS/MS based analysis, but also in the application of other technologies to analyze both native and therapeutic RNA. [9,10]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we reported other lowly modified sites in tRNA and rRNA, which demonstrates the high sensitivity of m 1 A-red-seq. However, m 1 A can spontaneously convert to m 6 A ( Suzuki et al 2020 ; Ammann et al 2023 ). This may affect accuracy, especially for lowly modified sites.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, NH 2 OH is incompatible with sequencing approaches that rely on mismatch calling. In contrast, chemical deacetylation of ac4C is a natural byproduct of alkaline hydrolysis protocols, though impacts on other modifications have been observed including the cytidine modification 3-methylcytosine (m3C) ( Ammann et al 2023 ). In addition, it is relatively inefficient at generating negative controls for ac4C sequencing: ∼40% of ac4C remains after a 3-h incubation at pH 10–10.5 with 100 mM sodium bicarbonate (NaHCO 3 ) ( Fig.…”
Section: Minimizing Residual Ac4c In Negative Controlsmentioning
confidence: 99%